Cover Feature: Reversing Size‐Dependent Trends in the Oxidation of Copper Clusters through Support Effects (Eur. J. Inorg. Chem. 1/2018). Issue 1 (29th December 2017) - Mammen, Nisha; Spanu, Leonardo; Tyo, Eric C.; Yang, Bing; Halder, Avik; Seifert, Sönke; Pellin, Michael J.; Vajda, Stefan; Narasimhan, Shobhana
Abstract : The Cover Feature shows the size‐dependent reduction temperature of oxidized subnanometer copper clusters supported on hydroxylated alumina. The reduction temperature decreases with cluster size for the supported clusters, in stark contrast with the opposite trend found for free gas‐phase clusters from first principles calculations. These findings underline the importance of cluster–support interactions and show ways of tuning, by size and support effects, the oxidation state of clusters, which can provide a handle to control their catalytic properties. More information can be found in theCommunication by S. Vajda, S. Narasimhan et al.